ChemInform Abstract: A Cascade Cross‐Coupling Hydrogen Evolution Reaction by Visible Light Catalysis. Issue 25 (24th June 2014) - Wu, Li‐Zhu; et al., et al.
Abstract The first example of a photocatalytic dehydrative cross‐coupling reaction employing two different C‐H bonds is described.